ANALISIS STRUKTUR BANGUNAN HOTEL 17 LANTAI DAERAH KEMAYORAN JAKARTA DENGAN PERMODELAN 3D SOFTWARE SAP2000 - Andrean Prasetiyo; Endah Kanti Pangestuti (DAS Institute, 2023)
There are lots of skyscrapers in Indonesia, especially in the Jakarta area. In designing the building, of course, it needs to be designed with appropriate earthquake loads for the location and conditions around the building. Regulations that can be used in the design of skyscrapers are regulations developed by the Indonesian National Standard (SNI), including earthquake loads, gravity loads, and design standards. The method of collecting data in research includes 2 things, namely, (1). primary data, in the form of style output in the SAP2000 version 20 application, Spcolumn v.6.0 column interaction diagrams, and the results of Microsoft Excel calculation analysis. (2) the secondary data obtained is in the form of an image of the structure of the 17 Floor Hotel Kemayoran Area Building.Secondary and primary data processing is in the form of remodeling the redesigned building structure design in SAP2000 version 20 and Spcoloumn v.6.0, determining the seismic design category, analyzing and making changes to the original building structure design that are not in accordance with SNI 1726: 2019 and SNI 2847: 2019. The results of the study found differences in the year versions in SNI 2847:2013 and 2847:2019, SNI 1726:2012 and SNI 1726:2019. In SNI 2847:2019 concerning structural concrete there is a change or addition of special detailing and stirrup reinforcement in columns, beams and floor slabs, while in SNI 1726:2019 concerning earthquake loads there is an increase in seismic forces.